CRIM-negative infantile Pompe disease, long-term observation of the effect of enzyme replacement therapy: a clinical case - D. R. Sabirova; D. I. Sadykova; A. A. Kucheryavaya; A. A. Kashina; L. A. Sabirova (Кубанский научный медицинский вестник, 2024)
Background. Infantile-onset form of Pompe disease (IOPD) comprises a progressive and fatal disease in the absence of pathogenetic treatment. Enzyme replacement therapy using biologically active recombinant human alglucosidase alfa is considered as a treatment option to increase the life expectancy of patients with early diagnosis and timely initiation of therapy.Case description. A child aged 5 months was delivered to the Cardiology Department of Children’s Republican Clinical Hospital (Tatarstan, Russia) for examination and clarification of the diagnosis. The patient’s parents complained of his shortness of breath, unproductive cough, cyanosis of the nasolabial triangle when restless, weakness, lethargy during breastfeeding session, as well as decreased appetite up to refusal to eat, constantly enlarged tongue. The examination revealed macroglossia and hypersalivation, pseudohypertrophy of calf muscles, dyspnea involving the accessory muscles, hepatomegaly, diffuse muscular hypotonia. Laboratory tests revealed an increase in alanine aminotransferase level greater than four times the normal values, aspartate aminotransferase level — more than nine times, a significant rise of creatine phosphokinase and lactate dehydrogenase, as well as natriuretic peptide. Echocardiography revealed significant myocardial hypertrophy of both the left and right ventricles. Complaints, medical history, clinical examination, and all of the above changes in laboratory and instrumental examinations suggested a group of hereditary metabolic diseases (Pompe disease), confirmed by a pronounced decrease in the activity of the alpha-glucosidase enzyme to 0.12 μmol/l/h in dry blood spots with subsequent molecular genetic study and detection of compound-heterozygous mutations in the GAA gene. It was decided to initiate specific enzyme replacement therapy by intravenous administration of a recombinant form of human acidic alpha-glucosidase (alglucosidase alfa) at a dose of 20 mg/kg/injection in a frequency of once every 2 weeks. In addition, CRIM (cross-reactive immunological material)-negative status determined immune tolerance therapy, including the most studied combination of three drugs: rituximab, methotrexate, and intravenous immunoglobulin, as a response to enzyme replacement therapy. Long-term observation of the effect of enzyme replacement therapy brought positive results in the form of new motor skills, decreased content of intracellular enzymes and natriuretic peptide, reduction of myocardial hypertrophy of the left and right ventricles. In the future, the child needs lifelong treatment.Conclusion. Awareness of physicians about Pompe disease will prevent the growth in diagnostic errors and neglected cases. In case of early confirmation, the effectiveness of currently available ERT increases: the possibility to stop the disease progression, to reverse its individual clinical manifestations, and to improve the patient’s quality of life.